HIV/AIDS Case Overview at Abdoel Wahab Sjahranie Regional Hospital Samarinda Year 2024 - Merry Andani; Vera Madonna Lumban Toruan; Rahmat Bakhtiar (Jurnal Ilmu Kesehatan, 2025)
Acquired Immunodeficiency Syndrome (AIDS) is a collection of symptoms or diseases It'scaused by the human immunodeficiency virus (HIV) infection. The Human Immunodeficiency Virus (HIV)infects and destroys Cluster of Differentiation (CD4) cells, making the CD4 count a useful measure formonitoring the immunological response to antiretroviral therapy (ART). This study aims to provide anoverview of HIV/AIDS cases at Abdoel Wahab Sjahranie Hospital in Samarinda in 2024. This observationalstudy utilized data from 58 medical records of HIV/AIDS patients obtained from the VCT clinic at AbdoelWahab Sjahranie Hospital in 2024. Based on age, the majority of cases were found in the productive agegroup of 25-49 years (72.4%), predominantly among males (69%), and with a marital status of previouslymarried (58.6%), indicating a tendency towards heterosexual risk groups. The majority of patients wereclassified in clinical stage 1 (34.5%) at initial examination, with most patients having a CD4 count withinthe range of 200-499 cells/mm³ at the time of diagnosis (58.6%), and had undergone ART for more than 5years (62.1%).